PEDIATRIC CHRONIC VIRAL HEPATITIS - THERAPEUTIC CONSIDERATIONS - Irina Dijmarescu; Daniela Pacurar; Dumitru Oraseanu (Amaltea Medical Publishing House, 2016)
Chronic viral hepatitis is a public health issue both worldwide and in Romania, where the prevalence of the disease is still high. We present the available therapies used for chronic viral hepatitis B treatment in children, worldwide and in Romania, indications and contraindications of treatment, benefits and disadvantages for each class. The present paper reviews only the treatment options and not profilactic measures for pediatric chronic viral hepatitis B. Currently, in Romania, standard Interferon is the treatment of choice. Entecavir is the only of the nucleotidic/nucleosidic analogues which is approved for children use, but not in those weighting less than 32.6 kg. Tenofovir, Adefovir and Lamivudine are not approved for pediatric chronic viral hepatitis B. Considering the fact that the disease progression is longer when the infection occurs earlier in life, efficient treatment is important for children with chronic viral hepatitis B. The availability of more treatment options provides a chance for patients who are nonresponsive to first line therapies.